Kesepian Digital pada Mahasiswa: Peran Problematic Internet Use dan Dukungan Sosial Digital - Yusak Kurniawan; Andik Matulessy; Nindia Pratitis (INSAN Jurnal Psikologi dan Kesehatan Mental, 2025)
The high use of social media as a means of social interaction can lead to loneliness within digital contexts. This condition is known as digital loneliness, which is when a person still feels lonely despite being active online. The purpose of this study is to determine the relationship between Problematic Internet Use (PIU) and Digital Social Support (DSS) with Digital Loneliness (DL) in college students who are active users of social media. The subjects of this study were college students aged 18-34 years selected using purposive sampling (N=250). The instruments used included PIU scale (α=0.747), DSS scale (α=0.863), and DL scale (α=0.934). Data analysis was performed using multiple linear regression. The results of the analysis showed that PIU and DSS were significantly related to DL. PIU was positively related to DL, while DSS was negatively related to DL. These findings indicate that a balance between the intensity of internet use and meaningful social support is needed to prevent DL.